Anti-Oxidants in Parkinson's Disease Therapy: A Critical Point of View - Filograna, Roberta; Beltramini, Mariano; Bubacco, Luigi; Bisaglia, Marco (Current neuropharmacology, 2016)
Parkinson's disease (PD) is a degenerative neurological syndrome, which is characterized by the preferential death of dopaminergic (DAergic) neurons in the Substantia Nigra. The pathogenesis of this disorder remains poorly understood and PD is still incurable. Current drug treatments are aimed primarily for the treatment of symptoms to improve the quality of life. Therefore, there is a need to find out new therapeutic strategies that not only provide symptomatic relief but also halt or reverse the neuronal damage hampering PD progression. Oxidative stress has been identified as one of the major contributors for the nigral loss in both sporadic and genetic forms of PD. In this review we first evaluate the current literature that links oxidative stress and mitochondrial dysfunction to PD. We then consider the results obtained through the treatment of animal models or PD patients with molecules that prevent oxidative stress or reduce mitochondrial dysfunction.